IMPLEMENTATION OF STEINER-PEDAGOGY IDEAS IN THE EDUCATIONAL PROCESS OF H.S. SKOVORODA KHARKIV NATIONAL PEDAGOGICAL UNIVERSITY - Іонова, О. (New Collegium, 2020)
The experience of using the ideas of Steiner-pedagogy in the educational process of H.S. Skovoroda Kharkiv National Pedagogical University is summa- rized and the effectiveness of the Waldorf approaches implementation in the following main directions is proved: professional training of the future teacher (introduction of special courses and courses by choice “The basis of Waldorf pedagogy” and “Anthroposophical education of adult”, the development of educational and methodological support of these disciplines); research work (defense of dissertations for the degree of doctor and candidate of pedagogical sciences; par- ticipation and management of the general scientific and methodological experiment of the all-Ukrainian level “Development of Waldorf pedagogy in Ukraine”; work of a creative research laboratory for the development and implementing of new pedagogical technologies); organization of the educational process in pre-school and general educational institutions on the Waldorf principles (establishment of the educational complex“School of free development”; scientific and methodo- logical support of the work of the Waldorf groups and classes in state educational institutions).